(untitled) - Jonathan Rigg (London, 1994)
The book deals with such topics as environment and development, plural societies, agrarian change, urbanization and primacy, natural resource development and land settlement. This book is a thematic contemporary human geography of the Association of Southeast Asian Nations (ASEAN) and has been written to fulffil two main objectives. First, to present an up-to-date statement covering some of the changes that are currently affecting the countries of the erea. And second, to provide an account that gives greater detailed discussion than would normally be found in a general, regional geography
Keywords: southeast asia - economic conditions,southeast asia - economic policy